Non-genetic factors affecting pre-weaning growth and survival rate in Barbari kids under semi-intensive management system - SINGH, MANOJ KUMAR; POUROUCHOTTAMANE, R; SINGH, SHIVA PRATAP; KUMAR, RAVINDRA; SHARMA, NITIKA; KUMAR, AKHILESH; DASS, GOPAL; PUNDIR, RAKESH K (The Indian Journal of Animal Sciences, 2022)
The effect of non-genetic factors on pre-weaning growth and survival performance in Barbari kids was assessed to maximize pre-weaning growth and survival rates. Performance records of 10,013 Barbari goats maintained at ICAR-Central Institute for Research on Goats, Makhdoom, Mathura, India, from 1995 to 2020 were analyzed for non-genetic factors. The effect of period and season of birth, type of births, sex of kids, parity of doe and dam’s 90- days milk yield were significant on birth weight and pre-weaning growth. Kids born in spring and winter had higher birth weight than those born in summer, monsoon and autumn, and maintained their superiority up to weaning. Male and single-born kids at birth were heavier than their counterparts and maintained superiority up to weaning. Significant linear association was observed in body weight at birth, 3 months and average daily weight gains with the increase in doe’s milk yield. Multiparous does produced kids with higher birth weight than primiparous does. Kidding in inclement seasons such as the peak of monsoon, summer and winter was associated with higher mortality. Autumn-born kids had the lowest pre-weaning mortality followed by the spring season. Higher mortality incidences were obtained in multiple-born kids, kids with low birth weight (<1.5 kg) and doe’s with low milk yield. The results suggest that to obtain higher growth and survival of kids, breeding should be planned to obtain maximum kidding during the spring and autumn seasons. Adequate care should be given to kids born from does with lesser milk yield, triplet or less birth weight, and for first 15 days of birth.